Steam barge MICHIGAN and native canoe next to dock, probably Vashon Island, approximately 1900 - Van Olinda, O. S. (Oliver Scott), 1868-1954 (1892)
The steam barge MICHIGAN was wrecked in 1909 on the Yukon River, Alaska. (pg. 165) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966). PH Coll 376.6G